Molecular tools for investigating immunohaematology problems. (April 2015) - Peyrard, T.
<x xml:space="preserve">Abstract</x> Blood types are classically determined by haemagglutination methods. However, several backgrounds represent limitations for serological techniques, which may be overcome by molecular testing, for example blood typing in recently transfused patients or in case of a positive IgG direct antiglobulin test when indirect antiglobulin testing is required for antisera. A multitude of molecular tools are available and can be separated in five groups: low‐throughput tests, medium‐ to high‐throughput assays, genomic DNA sequencing, high‐throughput DNA sequencing devices and other specialized techniques. The low‐throughput tests especially include PCR‐restriction fragment length polymorphism (RFLP) and manual allele‐specific PCR techniques. The medium‐to high‐throughput systems, mainly real‐time PCR, microarray DNA chips and mass spectrometry, allow for the testing of multiple different SNPs. The so‐called 'next‐generation sequencing' technologies can analyse 10 Mb to 1000 Gb per run. Their implementation in transfusion medicine is currently developed by a few teams worldwide, and they may become a major investigating tool in the next future. Standard genomic DNA sequencing may be used when genotyping assays are unavailable or when screening for common mutations by genotyping devices is inconclusive. Specialized techniques, reserved for complex cases or research, are performed after messenger RNA extraction, followed by reverse transcription into complementary DNA, which may be directly sequenced or cloned with plasmid vectors for single‐allele sequencing. Finally, electronic databases are also very helpful tools in molecular immunohaematology, for example the resources from the National Center for Biotechnology Information (NCBI), Rhesus Base and the ISBT Website of the Working Party on Red Cell Immunogenetics and Blood Group Terminology.